WEB APP FOR BANSOS DISTRIBUTION USING FINGERPRINTS AND PHOTO TIMESTAMPS FOR VERIFICATION AND MONITORING - Miri Ardiansyah; Aria Armada D.J; Farhan Hamdallah; Khoiriyah (LPPM Nusa Mandiri, 2026)
The implementation of fingerprint biometric sensors as a substitute for identity cards in the process of distributing social assistance is important because the requirement to bring an original or photocopy of an electronic identity card (E-KTP) is inconvenient for recipients. In addition to being inefficient, this method is also not in line with the government’s digitalisation initiatives. Furthermore, the distribution of social assistance is often perceived as slow in reaching beneficiaries. This study aims to develop a web-based information system for social assistance distribution that utilises fingerprint biometrics for recipient verification as a replacement for E-KTP, and incorporates a photo documentation feature with timestamps to record the time and location of distribution activities. The method used in this research is Research and Development (R&D). The novelty of this study lies in the integration of fingerprint authentication, photo timestamp evidence, and web-based monitoring within a single system for social assistance distribution. The results show that the developed system can validate recipient identities using fingerprints, provide timestamped photo evidence, support monitoring of distribution activities, and enhance transparency and efficiency in line with the government’s digitalisation programme.